Analysis of Ammonia (NH3) Levels in Cigarette Industry Wastewater in Pasuruan Regency as Environmental Quality Monitoring Using the Phenate Spectrophotometric Method - Reka Driananta Tresna Dewi; Indah Ardiningsih; Rinto Erwin Handoko (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the ammonia (NH3) levels in cigarette industry wastewater as an effort to monitor environmental quality at the Environmental Laboratory Unit of the Environmental Agency of Pasuruan Regency. The method used is phenate spectrophotometry based on the SM APHA 24 rd Ed. 5240 C.2023 standard, in which ammonia reacts with phenol and hypochlorite to form a blue indophenol complex compound measured at a wavelength of 640 nm. This research is descriptive quantitative in nature, utilizing a calibration curve as the basis for determining ammonia concentration in the samples. The analysis results show that the calibration curve has a good linear relationship with a coefficient of determination (R²) that meets the method validity requirements. The obtained data were then compared with wastewater quality standards according to applicable regulations to assess the level of pollution. Overall, the analysis of ammonia levels is important in supporting environmental pollution control and ensuring that discharged wastewater meets the established standards.